Prevalence and awareness regarding dental problem in school children at Jeddah City, KSA - Manal Rabee Abdullah Alghtani; Basoum ashour; Lama alhalees; Saif alyamani; Nazneen Mushtaq (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Dental caries is the most prevalent chronic disease affecting humans irrespective of age, sex, race and socioeconomic status. As around 90% of school children and most of the adults have been affected by dental caries, hence it has been considered as the most important global oral health burden . Epidemiological surveys are important for monitoring trends in dental caries and for assessing the dental needs. Methods: School children’s visited Primary care health care center during the study period ( Jan-2019- March-2019) of Jeddah city under 12 years of age were included in this study. Written consent was taken from them. A purposely constructed questionnaire was used to collect the data. SPSS ver.20 was used for analysis. Chi-square and t - test was used for analysis at 5% level of significance. Results: Total students included in this study was 178 with mean ± s.d was 7.5 ± 3.8 , 85% were aware about the dental problems. Conclusion: Need of reforms in dietary and brushing habits required